2012
DOI: 10.5740/jaoacint.cs2011_27
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Paralytic Shellfish Toxins in Shellfish by Receptor Binding Assay: Collaborative Study

Abstract: A collaborative study was conducted on a microplate format receptor binding assay (RBA) for paralytic shellfish toxins (PST). The assay quantifies the composite PST toxicity in shellfish samples based on the ability of sample extracts to compete with 3H saxitoxin (STX) diHCl for binding to voltage- gated sodium channels in a rat brain membrane preparation. Quantification of binding can be carried out using either a microplate or traditional scintillation counter; both end points were included in this study. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 2 publications
5
60
0
Order By: Relevance
“…Through the efforts of many, this hurdle has been overcome, partly by recruiting companies with radiolabeling facilities colocated in the same county as the means of toxin supply removing the initial international transfer. This has made the radiolabeled STX available for research as well as for use in bioassays for monitoring toxicity Robertson et al 2006;Van Dolah et al 2012) to prevent toxic seafood from entering the supply chain.…”
Section: Military Usementioning
confidence: 99%
“…Through the efforts of many, this hurdle has been overcome, partly by recruiting companies with radiolabeling facilities colocated in the same county as the means of toxin supply removing the initial international transfer. This has made the radiolabeled STX available for research as well as for use in bioassays for monitoring toxicity Robertson et al 2006;Van Dolah et al 2012) to prevent toxic seafood from entering the supply chain.…”
Section: Military Usementioning
confidence: 99%
“…the US FDA has established an action level for OA at 0.16 ppm, and it recommends "a commercially available immu-ing assay was carried out by van Dolah and coworkers (Van Dolah et al, 2012) and demonstrated an acceptable correlation with the MBA (slope of 1.64 and an r 2 = 0.84), and the HPlC detection method using precolumn oxidation (slope of 1.20 and an r 2 =0.92).…”
Section: Diarrhetic Shellfish Poisoning (Dsp)mentioning
confidence: 99%
“…Nevertheless, there are several attempts to develop assays on the basis of putative physods involving neuroblastoma cells (louzao et al, 2003Manger et al, 2003), an approach with rhodamine and synaptoneurosomes (Nicholson et al, 2002), and a patch clamp method (Velez et al, 2001). the radioactive method for saxitoxin analysis utilizing brain homogenates was recently accepted as an AOAC validated method (Van Dolah et al, 2012) and may be used for high-throughput screening of environmental samples (Doucette et al, 1997;Ruberu et al, 2003). the lOD of the latter method is reported at 2 µg Stxequiv./kg shellfish tissue.…”
Section: Functional Biochemical and Biomolecular Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Special shape materials such as scallops, which has no special classification devices at domestic and international [4]. A new classification device is recommended to meet the needs, which combines the advantages of spherical materials grading machine and makes up for its shortcomings [5]. According to the approximate diameter, scallops can be divided into four levels to facilitate the subsequent processing and marketing [6].…”
Section: Introductionmentioning
confidence: 99%